2017
DOI: 10.1038/aps.2017.165
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid levels with osteoporosis and bone turnover markers in a Chinese population

Abstract: Recent evidence shows that uric acid is protective against some neurological diseases, but can be detrimental in many metabolic and cardiovascular disorders. In this study, we examined the association between serum uric acid levels and bone metabolism in Chinese males and postmenopausal females. A total of 943 males and 4256 postmenopausal females were recruited in Shanghai. The levels of serum uric acid and bone turnover markers (BTMs) were detected along with other biochemical traits. In addition, the fat di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 35 publications
5
42
1
1
Order By: Relevance
“…A cross-sectional study, including 7502 healthy postmenopausal women found that serum SUA levels were positively associated with BMD at all sites [13]. In this line, similar results were those reported by Ishii et al (sample: n = 615) [14] and more recently by Yan et al (sample: n = 4256) [15]. In particular, in the latter study SUA was found to be positively correlated with BMD also in males (sample: n = 943) and associations with similar strengths and direction were reported in two other studies dealing with male subjects [25,26].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A cross-sectional study, including 7502 healthy postmenopausal women found that serum SUA levels were positively associated with BMD at all sites [13]. In this line, similar results were those reported by Ishii et al (sample: n = 615) [14] and more recently by Yan et al (sample: n = 4256) [15]. In particular, in the latter study SUA was found to be positively correlated with BMD also in males (sample: n = 943) and associations with similar strengths and direction were reported in two other studies dealing with male subjects [25,26].…”
Section: Discussionsupporting
confidence: 86%
“…A paradigmatic example in this context is serum uric acid (SUA), the most abundant non-enzymatic endogen antioxidant present in systemic circulation [12]. While recent studies have shown that SUA levels are positively correlated with bone mineral density (BMD) in the general population [13][14][15], contrasting results have been reported suggesting no associations between SUA and bone health markers [16], or marked differences in correlation strength and direction between men and women [17].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the highest sUA concentrations had a higher probability to develop dementia (OR 3.32, 95% CI 1.06--10.42) [103]. Contrarily, some studies revealed that HU might reduce the risk of neurological diseases, especially Parkinson's and Alzheimer's disease, vascular and non-vascular dementia [104] or osteoporosis [105]. This so-called "uric acid paradox" has already been widely discussed [4].…”
Section: "Uric Acid Paradox"mentioning
confidence: 99%
“…It has also been studied in bone formation, by stimulating osteoblasts and osteoclasts. Yan et al suggested that acid was negatively correlated with bone formation markers in postmenopausal females [27]. One possible explanation could be that the low level of uric acid might promote bone formation, especially the heterotopic ossification.…”
Section: Potential Biomarker and Related Pathway Analysismentioning
confidence: 99%